Extent and Characteristics of Woman Batterers among Federal Inmates - Goodwin, Beverly J.; Gondolf, Edward W.; Caraveo, L. Eduardo (International journal of offender therapy and comparative criminology, 2002)
Efforts to identify men who batter women in clinical settings have increased in recent years, but batterer research in United States federal prisons is lacking; low security federal prisons are logical places to consider batterer screening and treatment given the number of men, the domestic violence "risk markers" associated with these men and the likelihood they will be released and return to female partners. This study examined intake assessment data for 115 low security federal inmates. The inmates evidenced high levels of risk markers for woman battering, one in three (33%) acknowledged recent physical violence against women partners, 1 in 10 (13%) admitted severe violence, and the self-identified batterers showed more substance use and personality problems than other inmates. The findings suggest that batterer screening and treatment may be needed in federal prisons and that more research is warranted with a burgeoning male population that ultimately returns to society